FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PRODUKSI INDUSTRI PERABOT DI KECAMATAN JEUMPA KABUPATEN BIREUN - Agus Susanti; Devi Andriyani (LPPM Universitas Malikussaleh – Indonesia, 2019)
This study aims to analyze the Factors that Influence the Value of Furniture Industry Production in the Sub-district of Jeumpa District Bireuen in 2017. The data used in this study is secondary data. The method use to analyze the relationship of the dependent variable independently is the method of multiple Linear Regression Analysis. The results of the research are partially Labor and Investment Value have a positive and significant effect on the Value of Furniture Industry Production in the Sub-district of Jeumpa District Bireuen. Raw Material costs do not affect the Value of Furniture Industry Production in the Sub-district of Jeumpa District Bireuen. Simultaneously Labor, Investment Value and Raw Material Cost have a positive and significant effect on the Production Value of the Bireuen district of Jeumpa Sub-district Funiture Industry. The amount of influence is equal to 0,6080 or 60,80% . While the rest is influenced by other variables outside the model at 39,20 %.